Prevention of chain cleavage in the chemical synthesis of 2'-silylated oligoribonucleotides. - Wu, T (1989)
Strong aqueous ammonium hydroxide used to remove N-acyl protecting groups from synthetic oligoribonucleotides causes removal of some alkylsilyl protecting groups from 2'-hydroxyls and leads to chain cleavage. This problem is most severe when 30% ammonium hydroxide is used and substantially reduced but still detectable when 3:1 ammonium hydroxide-ethanol is used. We have virtually eliminated this unwanted cleavage by incorporating the labile phenoxyacetyl amino protecting group on adenosine and guanosine. The N-benzoyl protecting group remains adequate for cytidine nucleosides. Synthetic oligoribonucleotides containing these N-acylated nucleosides and 2'-t-butyldimethylsilyl or 2'-triisopropylsilyl protecting groups can be deacylated by room temperature treatment in saturated anhydrous methanolic ammonia (8-12 h) without causing any detectable chain cleavage.